Effect of foot orthoses on GRF in running gait : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Philosophy, Massey University - Sloane, John (Massey University, 2004)
For many years foot orthoses have been used to treat injuries of the feet, lower limb and back. Much of the evidence for their use has been anecdotal and measurement of kinematic or kinetic effects has been inconclusive. A single subject was selected for this case study to test the effect of orthoses on ground reaction forces during running. The subject was a competitive multi-sports athlete, and a heel strike runner (characterized as a runner who's heel is the first part of the foot to contact the ground). The experiment was conducted in a hall on a 40m curved running track with a force plate on one side. Timing lights were placed 5m from each end of the plate to measure speed and a video camera recorded the foot strike on the plate. The subject was asked to run at constant speed while wearing shoes and shoes with foot orthoses, at two self-selected speeds. Data from left and right foot was combined for analysis. The results showed a significant decrease in the magnitude of the vertical impact peak and the maximum vertical peak while the time to vertical impact peak was increased when wearing foot orthoses. Significant reductions were also seen in the peak posterior shear with both the time to peak and magnitude of the peak being changed by wearing foot orthoses. The mediolateral force was characterized by a medial impact followed by larger lateral impulse. It is the lateral force in the absorption phase of stance that is responsible for pronation, however no changes were seen in the mediolateral ground reaction force with the use of foot orthoses. This indicates that there is no acute effect in the shear forces, that act at approximately right angles to the subtalar joint axis. If orthoses have an acute effect on the lower limb it is likely to be complex and highly patient specific.
Keywords: Orthopedic apparatus; Ground reaction force (Biomechanics); Running shoes; Running